PENGARUH LATIHAN VARIASI TERHADAP KEMAMPUAN PASSING DAN STOPPING DALAM PERMAINAN SEPAK BOLA KLUB SMAN 1 SABAK AUH KECAMATAN SABAK AUH KABUPATEN SIAK - ', Setiadi; ', Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations conducted by researchers, that there are some problems or phenomena that occur in the game diklub SMAN 1 Sabak Auh, namely the lack of mastering technique of playing the ball. Such as passing and stopping in doing passing a lot of players make mistakes like not the right target, the ball is too slow and a lot of balls so that the ball did not get very easily taken up and controlled by the opponent. The purpose of this study was to determine the effect of exercise variations and Stopping Against Passing Ability Games Football Clubs In SMAN 1 Sabak Auh District Siak. The population in this study were as many as 16 people. The sampling technique is total sampling thus the sample in this study amounted to 16 people. Instruments used in this research is the ability of passing and stopping. Data were analyzed using t-test. Based uji- t produce tcount of 9.473 to 1.753 ttabel then H_a received, on the level of alpha (α) 0.05. It can be concluded that there is significant influence of exercise variations to the passing ability and stoping the game of football club SMA Negeri 1 Sabak Auh Subdistrict Siak. This suggests that the practice game this variation can be used to enhance the passing ability and stoping. Keywords: Exercise Variation, Passing and stoping